1985
DOI: 10.1111/j.1365-3083.1985.tb01431.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Amyloid Precursor SAA to Protein AA and Incorporation in Amyloid Fibrils in Vivo

Abstract: Experimental amyloidosis was induced in mice by intraperitoneal injections of endotoxin (lipopolysaccharide (LPS)). In addition to LPS, a group of mice received high-density lipoprotein (HDL)-SAA complexes isolated from human acute-phase serum, whereas a group of control mice received saline in addition to LPS. Isolated amyloid fibrils from the mice given HDL-SAA contained human AA protein, as shown by immunodiffusion, immunoblot, and enzyme-linked immunosorbent assay techniques, in addition to mouse AA. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
134
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(137 citation statements)
references
References 18 publications
3
134
0
Order By: Relevance
“…Furthermore, recent studies have also indicated that oral ERT increased risk of dementia. 21 SAA is a precursor of amyloid fibril, 22,23 which is found to deposit in the brain of patients with Alzheimer's disease, promoting chronic neuronal inflammation and neuronal loss. 24 Whether chronic elevation in SAA during oral ERT will lead to deposition of amyloid fibrils in brain tissue and contribute to development of dementia also remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have also indicated that oral ERT increased risk of dementia. 21 SAA is a precursor of amyloid fibril, 22,23 which is found to deposit in the brain of patients with Alzheimer's disease, promoting chronic neuronal inflammation and neuronal loss. 24 Whether chronic elevation in SAA during oral ERT will lead to deposition of amyloid fibrils in brain tissue and contribute to development of dementia also remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…SAA is deposited in the spleen, kidney, and liver, where it is processed, leaving the amino half to two thirds of its sequence behind in the fibril. 15,16 How SAA becomes deposited as an amyloid A protein (the 76 -amino acid N-terminal portion of SAA) is largely unknown; however, it is possible that its physiological carrier (see below) could contribute to this process.…”
mentioning
confidence: 99%
“…It is believed that persistently high levels of SAA during chronic inflammation may contribute to the occasional development of the potentially fatal disease reactive amyloidosis [amyloid A (AA) amyloidosis] (5). In AA amyloidosis, AA, an N-terminal (1-76) fragment of SAA (6), frequently is found to form amyloid deposits in the liver, kidney, and spleen. However, the presence, in vivo, of full-length SAA in amyloid deposits (7) and the ability of various SAA isoforms to form fibrils in vitro (8)(9)(10) suggest that proteolytic cleavage may not be a prerequisite for AA deposition but rather a postdeposition event.…”
mentioning
confidence: 99%